Functional outcomes of arthroscopic treatment of carpal tunnel syndrome - يوسف علي (Latakia University Journal -Medical Sciences Series, 2024)
Objective: Evaluate functional outcomes in treated patients and reduce complications that may occur. Materials and methods: A cross-sectional study was conducted on twenty patients treated in the orthopedic department at Tishreen University Hospital complaining of carpal tunnel syndrome in the years 2020 and 2022, where a detailed history and sufficient information were taken about each patient. Results: The results showed the prevalence of this syndrome in women with the dominant hand, especially at ages (41-60), and supported the improvement of symptoms during the three months following surgery and a return to work within a period of 13 days. There were few complications, including antithenar pain, hematoma, and one recurrence. Conclusion: Carpal tunnel syndrome is common in middle-aged females and in the dominant hand, and the incidence of complications after arthroscopic surgery is low.